Using all-cause mortality to define severe RV dilation with RV/LV volume ratio - Stephan P. L. Altmayer (Nature Portfolio, 2018)
Abstract Right ventricular (RV) end-diastolic volume (EDV) to left ventricular (LV) EDV ratio using cardiovascular magnetic resonance imaging (CMR) is an important parameter for RV size evaluation in additional to indexed EDV. We explore the severity partition for RV dilation using mortality in a population of 62 patients with pulmonary hypertension (PH). Cine short-axis images were acquired with a 1.5 T MR scanner using a steady-state free precession sequence. The optimal cutoff to classify severe RV dilation was determined by a receiver-operating curve (ROC) analysis based on mortality. We further defined mild and moderate categories by the standard deviation distance between normal and severely dilated and found the categories RV dilation by RV/LV volume ratio to be “mild” (1.27–1.69), “moderate” (1.70–2.29) and “severe” (≥2.30). There were significant differences in RVEDV and RV ejection fraction between “mild”, “moderate” and “severe” groups (p < 0.001). The “severe” category had a significantly higher mortality when compared to the “non-severe” categories (p < 0.001) while there was no difference among the “non-severe” dilated groups. We have shown that severe RV dilation partition can be defined using mortality with RV/LV volume ratio, which offers an outcome based grading of the “severe” category of RV dilation.